GASAB: STUDI ANALISIS AKAR MASALAH, DAMPAK DAN PENANGANAN - Hanif Maulaniam Sholah (LP3M IAI Al-Qolam Malang, 2019)
Al-Munawwariyyah Islamic Boarding School is a modern boarding school which provide complete and luxurious facilities. However, This Quranic Boarding school has the tradition of gasab. Gasab is the activity of taking, using and bringing any things belongs to other people without any permission from the owner. The result of interview between researcher and santri showed that not all of santris eager to do gasab. New santris are reluctant to do gasab although they are often becoming the victim of gasab because they are afraid to use anything belongs to other without any permission from the owner. Senior Santri is those who are often and eager to do gasab because they were tired if they have to buy any goods which is lost caused gasab. The effect of one gasab will encourage the other people to do one. Thus, this tradition will last long.